2017
DOI: 10.3892/or.2017.5821
|View full text |Cite
|
Sign up to set email alerts
|

Microarray expression profiles of long non-coding RNAs in germinal center-like diffuse large B-cell lymphoma

Abstract: Long non-coding RNAs (lncRNAs) are continuously transcribed and are involved in various cellular activities. However, their contributions to the occurrence and development of germinal center B-cell (GCB)-like diffuse large B-cell lymphoma (DLBCL) remain largely unknown. We applied microarray technology to profile the expression of lncRNAs in two different GCB-DLBCL cell lines (OCI-ly1 and OCI-ly19) and normal B lymphocytes. We demonstrated that 21,539 lncRNAs were expressed in all of the samples analyzed. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Recent studies have identified hundreds of DEGs in DLBCL [5]. However, the results of these studies have contradictory or inconsistent data due to small sample size [6], tissue heterogeneity or produced from single cohort studies [7]. Integrating and re-analyzing published sequence data may help resolve these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified hundreds of DEGs in DLBCL [5]. However, the results of these studies have contradictory or inconsistent data due to small sample size [6], tissue heterogeneity or produced from single cohort studies [7]. Integrating and re-analyzing published sequence data may help resolve these issues.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer research and recent studies implicated that various lncRNAs are dysregulated in human malignancies. Aberrant expression of lncRNA is associated with the DLBCL patient's clinical characteristics and poor prognosis and can be applied to serve as a therapeutic target [16][17][18]. LncRNA HULC has been reported to play a crucial role in tumor carcinogenesis and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNA (lncRNA) that is greater than 200 nucleotides has been reported to be associated with the development of lymphoma, including DLBCL [16][17][18]. Aberrant expression of lncRNA is associated with DLBCL occurrence and development.…”
Section: Introductionmentioning
confidence: 99%
“…Among these differentially expressed lncRNAs, ENST00000424690, ENST00000425358, and NR_026892 were upregulated, and ENST00000464929 and ENST00000475089 were downregulated in DLBCL compared to RLN. 104 Moreover, Deng et al demonstrated that NEAT1_1 could serve as a useful diagnostic tool to differentiate between DLBCL and lymphadenitis. 112 Several studies have reported the connection between lncRNA expression patterns and subtype classification.…”
Section: Potential Biomarkers For Diagnosis and Subtype Classificationmentioning
confidence: 99%